Pengaruh Supervisi Akademik Dan Budaya Organisasi Sekolah Terhadap Kinerja Guru - Nikmah, Nikmah; Saputra, Waldi; Latif, Abdul (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
The purpose of this study was to determine the effect of academic supervision and school organizational culture on teacher performance at SD IT Fadhilah Pekanbaru. The population in this study were teachers at SD IT Fadhilah Pekanbaru. This research method uses quantitative probablistic character using multiple regression analysis. The method used to analyze the data is multiple linear regression with a series of instrument tests and classical assumption tests. The sampling technique used is non-probability sampling, totaling 35 respondents who are teachers at SD IT Fadhilah Pekanbaru. The results of the study are from statistical calculations that the researchers did at SD IT Fadhilah Pekanbaru, it can be seen that the calculated F value is 37,419 at a significance level of 0.000, meaning that it can be ascertained that the Fcount is greater than the F table (3.28). This shows that the variables of Academic Supervision (X1) and Organizational Culture (X2) together have a significant effect on Teacher Performance (Y). Based on the value of the coefficient of determination shows the R2 value of 0.700. This means that the variable Teacher Performance is explained by the variables of Academic Supervision and School Organizational Culture of 70.0%, while the remaining 30% is influenced by other variables not observed in this study